Constructive and Unproductive Processing of Traumatic Experiences in Trauma-Focused Cognitive-Behavioral Therapy for Youth. Issue 2 (March 2017) - Hayes, Adele M.; Yasinski, Carly; Grasso, Damion; Ready, C. Beth; Alpert, Elizabeth; McCauley, Thomas; Webb, Charles; Deblinger, Esther
Abstract: Although there is substantial evidence to support the efficacy of cognitive-behavioral treatments (CBT) for posttraumatic stress disorder (PTSD), there is some debate about how these treatments have their effects. Modern learning theory and cognitive and emotional processing theories highlight the importance of reducing avoidance, facilitating the constructive processing of feared experiences, and strengthening new inhibitory learning. We examined variables thought to be associated with unproductive and constructive processing of traumatic experiences in a sample of 81 youth with elevated PTSD symptoms, who received Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) for abuse or traumatic interpersonal loss. Sessions during the trauma narrative phase of TF-CBT were coded for indicators of unproductive processing (overgeneralization, rumination, avoidance) and constructive processing (decentering, accommodation of corrective information), as well as levels of negative emotion. In previous analyses of this trial (Ready et al., 2015), more overgeneralization during the narrative phase predicted less improvement in internalizing symptoms at posttreatment and a worsening of externalizing symptoms over the 12-month follow-up. In contrast, more accommodation predicted improvement in internalizing symptoms and also moderated the negative effects of overgeneralization on internalizing and externalizing symptoms. The current study examined correlates of overgeneralization and accommodation. Overgeneralization was associated with more rumination, less decentering, and more negative emotion, suggesting immersion in trauma-related material. Accommodation was associated with less avoidance and more decentering, suggesting a healthy distance from trauma-related material that might allow for processing and cognitive change. Decentering also predicted improvement in externalizing symptoms at posttreatment. Rumination and avoidance showed important associations with overgeneralization and accommodation, respectively, but did not predict treatment outcomes. This study identifies correlates of overgeneralization and accommodation that might shed light on how these variables relate to unproductive and constructive processing of traumatic experiences. Highlights: Unproductive and constructive processing were examined in Trauma-Focused CBT for youth. We examined correlates of overgeneralization (OG) and accommodation (ACC), two predictors of treatment outcomes. OG was correlated with more rumination, negative emotion, and less decentering. ACC was correlated with less avoidance and more decentering, which predicted lower externalizing symptoms at outcome. These findings shed light on how OG and ACC might be associated with unproductive and constructive processing of traumatic experiences.